Photoinduced Synthesis of 2-Trifluoromethylated Indoles through Oxidative Trifluoromethylation Using Langlois’ Reagent in the Absence of External Photocatalyst - Das, Samarpita; Indurthi, Harish K.; Kumari, Amita; Sharma, Deepak K. (Synthesis, 2023)
A photoinduced approach for regioselective C-2 trifluoromethylation of indoles was achieved with CF3SO2Na under UV light irradiation (360–365 nm) at ambient conditions without any external photo activator. The key steps involve the in situ conversion of CF3SO2Na reagent to CF3• radical under oxygen or air and UV irradiation. This proficient method has the advantages of mild reaction conditions, fair substrate tolerability, and gram scalability.
Keywords: indole; Langlois reagent; trifluoromethylation; UV light irradiation; single electron transfer